Mesothelin expression in esophageal adenocarcinoma and squamous cell carcinoma and its possible impact on future treatment strategies. (May 2020) - Moentenich, Valeska; Comut, Erdem; Gebauer, Florian; Tuchscherer, Armin; Bruns, Christiane; Schroeder, Wolfgang; Buettner, Reinhard; Alakus, Hakan; Loeser, Heike; Zander, Thomas; Quaas, Alexander
Background: Mesothelin is expressed at very low levels by normal mesothelial cells but is overexpressed in several human cancers. This makes mesothelin a promising target for immunotherapy. Limited data exist about mesothelin expression in esophageal carcinoma. In a current clinical trial, the highly potent anti-mesothelin antibody anetumab ravtansine is used in patients with mesothelin-positive tumors. Response rates are correlated with mesothelin expression (using the Ventana antibody) in tumor cells. No data are available on expression levels using the Ventana antibody. Most data have been generated using the Novocastra antibody. As patients are selected for clinical trials based on antibody staining of tumor samples, a comparison of these two available antibodies is crucial. Methods: We analyzed 481 esophageal carcinomas [373 esophageal adenocarcinomas (EACs), 108 esophageal squamous cell carcinomas (ESCCs)] using two different monoclonal antibodies (Novocastra and Ventana) for mesothelin expression (low–mid and high-level expression, as used in one clinical trial). We also checked for the correlation of these results with clinical and molecular data. Results: We revealed different staining results for both antibodies in EACs: Ventana: 53.6% (low expression: 25.3%; high expression: 28.3%) and Novocastra: 35.7% (low expression: 21.2%; high expression 14.5%). In ESCC we found comparable staining results: Ventana: 13.3% (low expression: 9.5%; high expression: 3.8%) and Novocastra: 13% (low expression: 11.1%; high expression: 1.9%). ARID1a-deficient EAC patients demonstrated significantly higher rates of mesothelin-positive tumors than ARID1a intact EAC patients. No correlations were found with other molecular alterations ( TP53 mutation, ERBB2 amplification) or survival rates. Conclusion: To the best of our knowledge, this is the largest study analyzing the importance of mesothelin expression in esophageal carcinoma. This study revealed a significant number of mesothelin-positive esophageal carcinomas, especially adenocarcinomas. New therapeutic targets are urgently required to improve the outcome of patients with locally advanced or metastasized esophageal carcinoma. The inhibition of mesothelin can be a new attractive target.